The Milan System, from Its Introduction to Its Current Adoption in the Diagnosis of Salivary Gland Cytology - Esther Diana Rossi (MDPI AG, 2021)
Salivary gland masses are often encountered in the everyday practice of cytopathology. It is commonly known that the cytologic interpretation of these lesions can pose diagnostic problems due to overlapping cytomorphologic features. Fine needle aspiration (FNA) of salivary lesions shows good to excellent sensitivity and specificity in differentiating a neoplastic from a non-neoplastic process and in diagnosing common tumors such as pleomorphic adenoma. However, its value is limited in diagnosing specific neoplastic entities especially those with well-differentiated morphology. In light of this gap, an international group of pathologists has proposed a management-oriented, tiered classification for reporting salivary gland FNA specimens, "The Milan System for Reporting Salivary Gland Cytopathology (MSRSGC)". Similar to other classification systems, the MSRSGC scheme comprises six diagnostic categories, which were linked with a specific risk of malignancy (ROM) and management. In this review article, the author evaluated the published literature on FNA in diagnosing salivary gland lesions with the adoption of the Milan system since its introduction in the daily practice of salivary cytopathology.